Taste masking of ciprofloxacin by ion-exchange resin and sustain release at gastric-intestinal through interpenetrating polymer network - A. Michael Rajesh; Shreya A. Bhatt; Harshad Brahmbhatt; Pritpal Singh Anand; Kiritkumar Mangaldas Popat (Elsevier, 2015)
The aim of the study was to taste mask ciprofloxacin (CP) by using ion-exchange resins (IERs) followed by sustain release of CP by forming interpenetrating polymer network (IPN). IERs based on the copolymerization of acrylic acid with different cross linking agents were synthesised. Drug-resin complexes (DRCs) with three different ratios of drug to IERs (1:1, 1:2, 1:4) were prepared & evaluated for taste masking by following in vivo and in vitro methods. Human volunteers graded ADC 1:4, acrylic acid-divinyl benzene (ADC-3) resin as tasteless. Characterization studies such as FTIR, SEM, DSC, P-XRD differentiated ADC 1:4, from physical mixture (PM 1:4) and confirmed the formation of complex. In vitro drug release of ADC 1:4 showed complete release of CP within 60 min at simulated gastric fluid (SGF) i.e. pH 1.2. IPN beads were prepared with ADC 1:4 by using sodium alginate (AL) and sodium alginate-chitosan (AL-CS) for sustain release of CP at SGF pH and followed by simulated intestinal fluid (SIF i.e. pH 7.4). FTIR spectra confirmed the formation of IPN beads. The release of CP was sustain at SGF pH (<20%) whereas in SIF media it was more (>75%). The kinetic model of IPN beads showed the release of CP was non-Fickian diffusion type.